The Evolution of Amitraz and Its Metabolic Degradation Products in Human Blood over 90 Days for Use in Forensic Determination. Issue 9 (13th October 2020) - Chen, Yanmin; Zhao, Qingbiao; Guo, Hao
Abstract: Amitraz is a pesticide that is often involved in poisoning cases. In determination process of poisoning cases, a problem often encountered is that when the evidence samples were examined, the poison had already decomposed, thus posing significant difficulty for obtaining evidences. In this study, we qualitatively and quantitatively tracked the metabolic degradation products of amitraz and ascertained that the metabolic degradation products were N, N '-bisdimethylphenylformamidine, N '-(2, 4-dimethylphenyl)- N -methylformamidine (DMPF), 2, 4-dimethylformamidine (DMF) and 2, 4-dimethylaniline (DMA). It was found that although amitraz decomposed rather rapidly, the metabolic degradation products of amitraz persisted for quite a long time. This study demonstrates that forensic evidence in poisoning cases of amitraz can be obtained by the determination of DMPF, DMF and DMA. This study can provide insights on obtaining forensic evidences in poisoning cases.